The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1242/jcs.045567
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking proteasomal release of polyglutamine peptides initiates aggregation and toxicity

Abstract: Several neurodegenerative disorders, including Huntington's disease, are caused by expansion of the polyglutamine (polyQ) tract over 40 glutamines in the disease-related protein.Fragments of these proteins containing the expanded polyQ tract are thought to initiate aggregation and represent the toxic species. Although it is not clear how these toxic fragments are generated, in vitro data suggest that proteasomes are unable to digest polyQ tracts. To examine whether the resulting polyQ peptides could initiate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 47 publications
1
57
0
Order By: Relevance
“…However, it remained unclear whether expanded polyQ stretches embedded in native polyQ protein sequences like mHtt-exon1 are also inefficiently degraded by proteasomes in living cells. In the case of remaining polyQ stretches as partial cleavage products of incomplete proteolysis, these fragments would accumulate within the cell and start to aggregate, as previously shown in living cells expressing pure expanded polyQ peptides without flanking sequences (23).…”
Section: Mhtt-exon1 Ismentioning
confidence: 60%
See 3 more Smart Citations
“…However, it remained unclear whether expanded polyQ stretches embedded in native polyQ protein sequences like mHtt-exon1 are also inefficiently degraded by proteasomes in living cells. In the case of remaining polyQ stretches as partial cleavage products of incomplete proteolysis, these fragments would accumulate within the cell and start to aggregate, as previously shown in living cells expressing pure expanded polyQ peptides without flanking sequences (23).…”
Section: Mhtt-exon1 Ismentioning
confidence: 60%
“…The Htt-exon1-25Q-GFP construct was kindly provided by R. Kopito (Stanford University). GFP-Ub, GFP-Ub-Q112, and Ub-Q112 were generated as described previously (23). Ub-G76V-GFP was a kindly provided by N. Dantuma (Karolinska Institute, Stockholm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it remains unclear whether these nuclear structures are storage depots for misfolded proteins or are actively engaged in degrading misfolded proteins. Previous studies reported that N/Q-rich proteins cannot be degraded efficiently by the proteasome (74)(75)(76), unless proteasomal activity is increased (77). Therefore, we speculate that D. discoideum has evolved mechanisms to efficiently degrade and prevent the aggregation of prion-like proteins.…”
Section: Discussionmentioning
confidence: 83%